Estimating diversity of crabs (Decapoda: Brachyura) in a no-take marine protected area of the SW Atlantic coast through DNA barcoding of larvae. Issue 3 (3rd May 2016) - Brandão, Manoela C.; Freire, Andrea S.; Burton, Ronald S.
Abstract : DNA barcoding was used to identify crab larvae from the Marine Biological Reserve of Arvoredo, encompassing a coastal archipelago off the SW Atlantic coast (27°S, 48°W). Partial mitochondrial COI or 16S rRNA gene sequences were obtained for 488 larvae, leading to the identification of 20 species. The COI sequences generated 13 barcode index numbers (BINs) within Barcode of Life Data Systems (BOLD), among which 11 were concordant with single species. DNA from ∼ 6% of the larvae did not amplify using the primers tested; based on external morphological characteristics, these larvae represented four possible additional operational taxonomic units (OTUs) at the family level. Intraspecific variation for the COI and 16S rRNA genes was found to be < 2.6% and < 2.1% respectively (Kimura 2-parameter distance), whereas interspecific divergence ranged from 7.9% to 21.5% and 6.4% to 14.5%, respectively. These results imply that both genes are suitable for use in species identification of brachyuran crabs of this area. Molecular identification of this group successfully enabled the diagnosis of larvae of closely related species, including congeners in Mithrax, Achelous and Callinectes . In addition, eight out of 20 species recognized represent new records for the reserve suggesting that the brachyuran fauna in the area has been underestimated based on traditional biodiversity measures. The availability of primers suited to the targeted species, and the development of a taxonomically comprehensive DNA barcoding database are the major recommendations to improve the accuracy and feasibility of using DNA barcoding for species identification of SW Atlantic brachyuran crabs.